Influence of short video content on consumers purchase intentions on social media platforms with trust as a mediator - Luo, Chengdan; Mohd Hasan, Nurul Ain; Zamri bin Ahmad, Abdul Mua’ti; Lei, Guosheng (Nature Research, 2025)
Short videos on social media platforms have boomed with the rapid growth of the video consumption industry and have become an important marketing tool for businesses. With the rise of platforms such as TikTok or Douyin, short videos have profoundly impacted consumer behavior, making it crucial to understand their role in shaping consumer purchase intention. However, there is still a need for further research on how short video content promotes consumer purchase intent. Based on the Stimulus–Organism–Response (SOR) model, this study constructs a structural model to explore the impact of short video content on consumer purchase intention, focusing on the mediating role of consumer trust. The model incorporates usefulness, ease of use, and entertainment as external stimuli, consumer trust as internal psychological responses, and purchase intention as the final behavioral outcome. This study collected 372 valid data from Chinese consumers through an online questionnaire and empirically analyzed it using structural equation modeling. The study results show that short-form video content’s usefulness, ease of use, and entertainment significantly affect consumers’ trust and purchase intention. Moreover, consumer trust positively affects purchase intention and mediates the relationship between short video content and purchase behavior. This research extends the application of the SOR model to the context of social media short videos, highlighting the crucial role of consumer trust in shaping consumer purchase decisions. Based on these findings, we propose actionable strategies for businesses to optimize short video content and build consumer trust, ultimately enhancing marketing effectiveness and driving consumer purchases.